PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GRUP INVESTIGASI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS V UPT SDN 037 KARYA INDAH - Mutiara Nur Afifah; Laili Rahmi (STKIP Subang, 2026)
This study aims to improve the Mathematics learning outcomes of fifth-grade students at UPT SDN 037 Karya Indah through the implementation of the cooperative learning model Group Investigation (GI). This Classroom Action Research was conducted in two cycles, each consisting of two meetings. The research procedures included planning, action implementation, observation, and reflection. The instructional material focused on prism geometry in the first cycle and cylinder geometry in the second cycle. Data were collected through observations of teacher and student activities as well as assessments of student learning outcomes. The findings indicate a consistent improvement in learning mastery. Prior to the intervention, the mastery level was 33.33%. In cycle I, it increased to 63.33% in the first meeting and 73.33% in the second meeting. In cycle II, mastery rose to 80% in the first meeting and reached 86.67% in the second meeting. These results demonstrate that the Group Investigation model enhances student engagement, strengthens conceptual understanding, and significantly improves learning outcomes.